2022
DOI: 10.1186/s12873-022-00697-3
|View full text |Cite
|
Sign up to set email alerts
|

Paramedic use of the Physician Order for Life-Sustaining Treatment (POLST) for medical intervention and transportation decisions

Abstract: Background Physician Order for Life-Sustaining Treatment forms (POLST) exist in some format in all 50 states. The objective of this study is to determine paramedic interpretation and application of the California POLST for medical intervention and transportation decisions. Methods This study used a prospective, convenience sample of California Bay Area paramedics who reviewed six fictional scenarios of patients and accompanying mock POLST forms. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…It was observed across all three levels of German EMT education. The interviews in this study revealed similar findings to those of Breyre regarding emotional overload ( 25 , 26 ); however, our study revealed a significantly greater emotional burden in emergencies involving children with life-limiting conditions.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It was observed across all three levels of German EMT education. The interviews in this study revealed similar findings to those of Breyre regarding emotional overload ( 25 , 26 ); however, our study revealed a significantly greater emotional burden in emergencies involving children with life-limiting conditions.…”
Section: Discussionsupporting
confidence: 84%
“…An important part of the future guideline is to inform the participants about the importance and the limitations of decision making. DNR orders or Physician Order for Life-Sustaining Treatment (POLST) forms can help in making these decisions ( 26 ). In a qualitative study on a group of 15 EMTs and paramedics, the participants stated that formal training was needed to better prepare them for the emotional aspects of communicating with patients and their families, to handle grief, and to obtain advice in decision making ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…If CPR is not contraindicated and the parents don’t disagree, then advanced life-support (ALS) should be started until the EMS team gets new information. DNR orders or Physician Orders for Life-Sustaining Treatment (POLST) forms can help the EMS make decisions ( 43 ).…”
Section: Discussionmentioning
confidence: 99%